Bidirectional Battery Interface in Standalone Solar PV System for Electrification in Rural Areas - Yuwono Bimo Purnomo; F. Danang Wijaya; Eka Firmansyah (IJITEE (International Journal of Information Technology and Electrical Engineering), 2021)
In a standalone photovoltaic (PV) system, a bidirectional DC converter (BDC) is needed to prevent the battery from damage caused by DC bus voltage variation. In this paper, BDC was applied in a standalone solar PV system to interface the battery with a DC bus in a standalone PV system. Therefore, its bidirectional power capability was focused on improving save battery operation while maintaining high power quality delivery. A non-isolated, buck and boost topology for the BDC configuration was used to interface the battery with the DC bus. PID controller-based control strategy was chosen for easy implementation, high reliability, and high dynamic performance. A simulation was conducted using MATLAB Simulink program. The simulation results show that the implementation of the BDC controller can maintain the DC bus voltage to 100 V, have high efficiency at 99.18% in boost mode and 99.48% in buck mode. To prevent the battery from overcharging condition, the BDC stops the charging process and then works as a voltage regulator to maintain the DC bus voltage at reference value.